Discourse on Islamic education and Islamization - Rahath House, Yousef (The Islamic Cultural Centre & The London Central Mosque, 2016)
The purpose of this article is to put into context the contemporary Muslim educational discourse, especially the concept of the Islamization of knowledge by reference to the previous Muslim educational debates. Tracing back to the roots of the discourse is intended not to validate a particular approach, but to shed light on the socio-historic landscape that played a significant role in shaping the past and present discourse on Islamic education. Inasmuch as interest in Islamic education has led Muslim scholars and intellectuals to produce a large body of literature, in order to have a bigger picture of colonial and post-colonial Muslim discourse on education the works of some prominent scholars who participated in the discourse of Islamic education have been chosen. The analysis on different Islamic educational trends identifies some of the resemblances and divergences between the past and the present.